EFFECTS OF NATURAL PRODUCTS ON ORAL HEALTH: A REVIEW - Nivetha, Raja; Murthykumar, Karthikeyan; Ks, Ashwin; Kumar, Nirmal; R, Priyadharshini (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The use of plant products to improve dental health and to promote oral hygiene is in exist long since. A rise in the use of sugar diet, bakery products and carbonated drinks increase the prevalence of dental caries. Lack of oral hygiene result in accumulation of  plaque and calculus, which is the major etiology factors for gingivitis and periodontitis. Undoubtedly, the natural products is the source for most of the pharmaceuticals. A range of treatment modalities are available for the treatment of different oral diseases. The frequent use and misuse of currently available  therapeutic agents has led to the evolution of increased incidence of adverse effects and development of resistant strains. Hence the search for alternative option continues. This article aim to review the efficacy of   natural products like turmeric, camphor and clove in maintaining oral health in particular and overall health in general.